Relationship between tobacco use and body mass index- a propensity score matching analysis of an indian National Survey - Madhur Verma; Nitin Kapoor; Ajit Kumar Jaiswal; Prakash Kumar; Pritam Halder; Vandana Esht; Waseem Mumtaz Ahamed; Omna Singh; Rakesh Kakkar; Sanjay Kalra; Sonu Goel (PLoS ONE, 2025)
Background Tobacco and obesity control is among the major health priorities. Previous studies have mixed opinions about their association. The present study was done to investigate the association between Body Mass Index (BMI) and tobacco use (smokers, smokeless tobacco users and dual users) among Indian adults. Methods Secondary analysis of the fifth National Family Health Survey (2019–21) was conducted that included 724,115 women (15–49 years) and 101,839 men (15–54 years). Nutritional status (BMI) was dependent variable. Current tobacco use was primary independent variable. Using sampling weights, bivariate analysis assessed the association, the determinants were explored using the binary logistic multinomial regression. Propensity Score Matching (PSM) was employed using STATA software to control for potential confounding and strengthen causal inference. Results Weighted prevalence of overweight/obesity and underweight was 38.17%, and 18.05%. Underweight prevalence was highest in smokeless tobacco users (17.09%). Overweight/obesity was highest among smokers (41.62%). Compared to non-users, tobacco users had higher odds of being underweight (AOR: 1.2; 95% CI: 1.2–1.2) and lower odds of being overweight (0.9; 0.9–0.9). PSM confirmed the BMI lower effect of Tobacco (ATT: 0.159), with a non-significant impact on overweight/obesity (ATT: -0.360). Conclusions We present clear evidence that tobacco use, especially smokeless forms, is significantly associated with undernutrition among Indian adults, while its impact on overweight/obesity remains minimal, which otherwise was more common in smokers. The findings clarify the previously mixed evidence and highlight the nutritional impact of tobacco, reinforcing the need for integrated interventions targeting both tobacco cessation and nutritional improvement.